Sinkretisme Islam di Madura : Sebuah pembacaan Singkat Ritus Macopat di Sumenep Madura (LPTNU Sumenep, 2022)
This paper will describe the macopat rite in Sumenep Madura, assuming that the macopat tradition is well developed and is an effective medium in the spread of Islam in Sumunep by the guardians and sponsored by the palace in the use of the ancient Javanese language (kawi). Thus, this brief research can at least answer the question, namely: What is the macopat tradition in Sumenep Madura? and how is the element of Islamic syncretism in the macopat tradition in Sumenep Madura?. By using the library research method to inventory references about macopat that have been studied by previous researchers both at home and abroad who discuss the elements of syncretism by browsing various literatures. The term